MOOC SK4e - Skills for employability - Pinto, Paula (2020)
This Massive Online Open Course aims to facilitate the development of intrapersonal and interpersonal skills important to meet the needs of today’s professional environment and maintain work-life balance. The course is structured in three modules: Module 1 - Soft skills in professional environment; Module 2 - Self-leadership; Module 3 - Communicate efficiently. Completion of all activities is achieved in seven weeks, after which, the participant earns a certificate. The design of the course was based on project TRANSPEER: A transnational skills programme to enhance the employability of researchers (site: https://transpeerdevelopment.org/)